Study and Analysis of the Impact of Man-in-the-Middle (MITM) Attacks on the Software-Defined Network - محمد صبيح; عبير حسن (Latakia University Journal -Engineering Sciences Series, 2022)
Software Defined Networks SDN is a new technology in managing computer networks, and it is the most studied topic in recent years, as it has provided many features and contributed to solving many problems experienced by traditional networks. However, what has not changed is the need to understand the network topology and stay informed about how network elements perform across the topology. This factor continues to be a key factor in achieving performance and security goals. The SDN architecture offers a lot of advantages to the networking field, but its weaknesses mostly lie in the lack of security. However, it provides support for security solutions, an area that is currently being explored by many researchers, and this is what made the study of the security aspect by achieving the man-in-the-middle attack in several forms and studying its impact on the network and studying security solutions and proposing a new structure that specializes in detecting and repelling these attacks . Therefore, in this paper, we will study the security issues of a number of widely used controllers specifically regarding man-in-the-middle attacks, and we will study the most important attack detection and blocking algorithms.